FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN MEMBELI PRODUK VETSIN (Studi Kasus : Ajinomoto, Masako, dan Royco) - Nofiawaty Nofiawaty (Politeknik Negeri Sriwijaya, 2012)
The study was conducted to determine what factors influence consumer decision to purchase Vetsin (MSG). Object of study is the Ajinomoto brand, Masako and Royco. This study used a descriptive conclusive research in the form of a single cross-sectional sample of 120 respondents who were in the city of Palembang. Factor analysis is used to categorize the variables that are considered to have certain similarities, and the factors examined based on the components of the marketing mix. The results obtained in this study are different factors that influence consumer decisions on any brand. At Ajinomoto brand formed 3 factors, 2 factors Masako brand and Royco 2 factors.